Effect of Stcr Based Fertilizers and Manure Application on Soil Properties, Yield and Economics of Turmeric in Acid Alfisol of Himachal Pradesh - Shubham; Dixit, S. P.; Sharma, S. K. (International Journal of Economic Plants, 2020)
The study was primarily devoted to assess the effect of different levels of NPK fertilizers with or without farmyard manure on soil properties, rhizome yield and economics of turmeric. A field experiment was laid for eight treatments comprised of different levels of NPK alone or in combination with FYM in a completely randomized block design with three replications. The results showed that application of NPK fertilizers as per STCR with FYM@ 5t ha-1 for targeted yield 40 t ha-1 resulted maximum soil organic carbon (9.03 g kg-1), soil available NPKS (392, 42.1, 194 and 23.3 kg ha-1, respectively). Maximum nutrient concentration and uptake in rhizome and straw were also higher in STCR based treatments over traditional methods. Rhizome yield (231 q ha-1) and straw yield (16.1 q ha-1) were also found to be maximum in the same treatment, whereas, the maximum benefit-cost ratio of 3.15 was recorded in the treatment of STCR based target yield of 20 t ha-1 followed by soil test based (3.04) treatment and least (1.97) in absolute control.